ANALISIS SISTEM PENGADAAN BARANG DAN JASA (PENUNJUNG LANGSUNG) PADA DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA MANADO - Faisal, Nur Ilmi; Morasa, Jenny; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2017)
Product and service supplies in government instance is one of activities to increase performance of government instance in order to achieve the expected goal that is absortion of the effective and efficient budet. Government regulation No. 5 of 2015 about the fourth amendment of government regulation No. 54 of 2010 abour government product and service supplies become a guidelines for each government instance in particular in this case, Satuankerjpeangkatdaerah will be the executor of government product and service supplies, in particular, the direct appointment on department of public works and land use of Manado city of 2016. This research use qualititativemethod. The result of this research show that product and service supplies in department of public works and land use of Manado city in particular, the direct appointment of supply official car already suitable with the riles and regulations that applicable and always up to date and innovation in carrying out the activity of product and service supplies in department of public works and land use of manado city. Because of that, product or service supplies in Departement of public works and land use of manado city for the better guided by the govement regulation that has been set.Keywords : Procurement of Governmental Services, Direct Appointment